Pengaruh Tepung Beras Pragelatinisasi terhadap Penyerapan Minyak dan Sensori Kue Cucur - Putri Novita Savitri; Elvira Syamsir; Slamet Budijanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Cucur is a traditional food with oily appearance,which may affect the sensory acceptance. Thus, in this research we attempted to reduce its oil absorption by using pregelatinized rice flour as the ingredient for cucur dough. The type of rice and temperature of extrusion process affect the characteristics of pregelatinized rice flour and final products. Thus, the objective of this research was to determine the effect of using pregelatinized rice flour on the oil uptake and sensory of cucur. The type of rice used were IR64 and IR42, and the extrusion process temperatures were 130 and 150°C. The oil uptake by cucur made with pregelatinized rice flour was analyzed during deep frying and sensory analysis was done on the resulting cucur. The results showed that the type of rice, temperature of extrusion, and their interactions had a significant effect on the characteristics and sensory of cucur. A combination of IR42 and 150°C resulted in cucur with 35.97% moisture content, 19.32% fat content, 18.14% moisture loss, 18.14% oil uptake, while the overall sensory attribute was acceptable to the panelists. Use of pregelatinized rice flour resulted in decrease in the oil uptake and moisture loss. Cucur made with pregelatinized rice flour has desirable intensities of sensory attributes (appearance, flavor, texture, and mouthfeel), which result in the higher overall preferences score.